Certified Kubernetes security specialist (CKS) course. - Sharma, Himanshu (Packt Publishing, 2022)
Become a certified Kubernetes security specialist by taking up this complete hands-on course About This Video Deep technical insight into Kubernetes Learn to use kubesec to perform static analysis using Docker image Learn how to use Falco to find malicious processes In Detail This Kubernetes Security Specialist course provides foundational knowledge using concepts and hands-on demonstrations of the Kubernetes Cluster. In this course, we will be focusing more on the practical side, so make sure you have a running Kubernetes cluster. This course is focused on security. It deals with all aspects of security within the context of a Kubernetes environment. That means securing not only the Kubernetes cluster itself but also the applications running within the cluster. You will learn how to secure many different components of Kubernetes applications and environments. We are going to cover every topic such as cluster setup, creating an ingress, and securing an ingress. You will also learn cluster hardening, which includes RBAC, role, and role binding for a user. Further, you will learn system hardening, kernel hardening, minimizing microservice vulnerabilities, supply chain security, monitoring, logging, and runtime security. By the end of this Kubernetes course, you will gain in-depth knowledge about Kubernetes and be a Kubernetes security specialist. Audience This Docker course is designed for Kubernetes administrators, security specialists, and for those who want to master Certified Kubernetes Security Specialist. You should already have some Kubernetes Administrator knowledge before attending this course.